2006
DOI: 10.1021/cm061783b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Top Crust of Entangled Nanotubes on the Structure of Vertically Aligned Forests of Single-Walled Carbon Nanotubes

Abstract: The time evolution of the growth process of vertically aligned single-walled carbon nanotubes (or V-SWNTs) on a flat substrate was examined by scanning electron microscopy (SEM), resonant Raman spectroscopy, and angle-resolved X-ray absorption near-edge structure (XANES). This detailed characterization gives evidence for the growth of a thin layer (crust) of randomly oriented single-walled carbon nanotubes during the first stages of the growth process. This crust is responsible for the unique forest-like morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…The measured, single-walled CNT films have a disordered and dense crust layer on top of an aligned middle region. This is similar to observations of multiwalled CNT films in past work (21,27,34). Our single-walled CNTs have been observed to be denser and stiffer due to a smaller diameter as well as better quality.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The measured, single-walled CNT films have a disordered and dense crust layer on top of an aligned middle region. This is similar to observations of multiwalled CNT films in past work (21,27,34). Our single-walled CNTs have been observed to be denser and stiffer due to a smaller diameter as well as better quality.…”
supporting
confidence: 91%
“…Our previous data for the thickness-dependent in-plane modulus of multiwalled CNT films indicated a strong dependence on the nanotube density and alignment (21), which are linked to the detailed growth details (26)(27)(28). Other approaches, such as mesoscopic simulations or atomistic models, found that CNT networks exhibit unique self-organization, including bending and bundling (29)(30)(31).…”
mentioning
confidence: 96%
“…A similar rippling pattern can also occur on forests (composed of initially straight nanotubes) that are intentionally subjected to externally applied mechanical compression ex situ [9][10][11]. The interactions between nanotubes have previously been shown to be important for forest morphology [6][7][8][12][13][14][15][16][17][18][19], and will be considered here.…”
Section: Introductionmentioning
confidence: 71%
“…A variety of synthesis conditions have proven effective for preferential vertical growth. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, CNTs with a desired form of yarn are promising for future textile electronics. Several methods have been tried to produce CNT yarns.…”
Section: Introductionmentioning
confidence: 99%